In vitro evaluation of hypochlorous acid-silver nanoparticle waterline disinfectant for dental unit waterline disinfection - Tingting Yin; Qiaowen Li; Huan Sun; Jin Zheng; Yuanyuan Wang; Yi Luo; Li Wang (BMC Chemistry)
Abstract Background This work intended to assess the disinfection efficacy of hypochlorous acid (HA) and silver nanoparticles (AgNP) disinfectants in disinfecting the dental unit waterlines (DUWL) during comprehensive oral treatment and explore their potential applications in the oral medical environment. Methods: Firstly, AgNP solution was prepared and evaluated through X-ray diffraction (XRD), field emission transmission electron microscope (FE-TEM), and stability tests. Subsequently, 15 dental units were selected and randomly assigned to three groups, each receiving a different disinfection method. Specifically, one group (5 units) received HA disinfectant (HA group), one group (5 units) received AgNP disinfectant (AgNP group), and another group (5 units) received a combination of HA and AgNP disinfectant (HA + AgNP group). Bacterial counts before and after disinfection were compared and analyzed at four sites on the dental units: high-speed handpiece tubing, mouthwash, ultrasonic scaler, and three-way syringe. Results The growth of biofilm on the waterlines was observed using scanning electron microscopy (SEM) and laser confocal microscopy (LCM). The results indicated that AgNP solution was successfully prepared and demonstrated excellent stability. There was no significant difference in the average weekly number of patients treated across the three groups (P > 0.05). After disinfection, bacterial counts were significantly reduced in all groups. Compared to the HA and AgNP groups, the HA + AgNP group exhibited a markedly lower bacterial count, with statistical significance (P < 0.05). The compliance rates observed during the first disinfection and two weeks post-disinfection were slightly lower in the HA and AgNP groups compared to the HA + AgNP group, although no significant statistical difference was found (P > 0.05). SEM images revealed uneven biofilm plaques on the inner surface of the pipes prior to disinfection, embedded within a dense matrix, while the biofilm was visibly disrupted post-disinfection. LCM software analysis showed that, compared to the HA and AgNP groups, the HA + AgNP group had a significantly lower percentage of live bacteria on the biofilm post-disinfection (P < 0.05). Conclusion Compared to any single disinfectant regimen, the combined use of HA and AgNPs effectively inhibited bacterial growth and exerted a significant destructive effect on biofilms. Therefore, this combination is expected to be a viable option for disinfection of DUWL in the oral healthcare setting. Clinical trial number Not applicable.